EFFECTS APELIN-12 AND OBESTATIN OF LEFT VENTRICULAR HYPERTROPHY IN PATIENTS WITH ARTERIAL HYPERTENSION DEPENDING ON THE DURATION OF DIABETES MELLITUS TYPE 2 - Кравчун, П.Г.; Табаченко, О.С. (World of Medicine and Biology, 2015)
Аrterial hypertension and diabetes mellitus at this time are the most common diseases in the world according to WHO reports. Arterial hypertension and diabetes mellitus - are interrelated diseases, which have powerful addictive action, directed to several target organs with the rapid development of complications. Apelin-12 - adypocytokine which shows hypotensive and inotropic effects, stimulates glucose utilization and has antiatherogenic properties. There is evidence that apelin deficiency in the body is associated with the development of heart failure, аrterial hypertension and diabetes mellitus. Obestatin - a hormone secreted by cells of the stomach and intestine, was opened in 2005 by employees of the Medical Faculty at Stanford University by computer analysis of the human genome. Receptor obestatin - GPR39 - found in the periphery and in the central nervous system, its content in plasma decreases during fasting. Study of l obestatin’s level in plasma gives reason to use these data in the diagnosis and treatment of certain diseases: obesity, diabetes mellitus type 2, Prader-Willi syndrome and irritable bowel syndrome. But the problem apelin-12 and obestatin changes in patients with аrterial hypertension combined with diabetes mellitus type 2 based on the presence of left ventricular hypertrophy and duration of metabolic disorders is the topic of scientific debate.The aim - to assess the presence and character of the relationship between apelin-12, obestatin and cardiohemodinamic parameters for analyzing the effects of these humoral markers on of left ventricular hypertrophy in patients with arterial hypertension and diabetes mellitus type 2.Object and methods. The study examined 105 patients with arterial hypertension, 75 patients from them had a combination of arterial hypertension and diabetes mellitus type 2 (mean age 57,03 ± 1,17), and 30 hypertensive patients without diabetes mellitus type 2 (average age 57,1 ± 2,23). The main group of patients who had comorbidity of hypertension and type 2 diabetes were divided into subgroups depending on the duration of type 2 diabetes. The first subgroup consisted of patients with duration of diabetes mellitus type 2 less than 5 years (23 patients, 31%), the second subgroup – less than 10 years (35 patients, 47%), and the third subgroup - more than 10 years respectively (16 patients, 22%).Apelin-12 and obestatin determined using ELISA commercial test kits «Human Apelin 12 (AP12) ELISA Kit» and «Human Obestatin (OB) ELISA Kit», China. Statistical analysis of the data was carried out using the statistical software package «Microsoft Excel». Data are presented as mean values and error of the mean. Statistical significance was determined at various F-Fisher criterion. Analysis of relationships conducted using Spearman correlation (r).Expression of left ventricular hypertrophy on the left ventricular mass index increased in proportion to the duration of diabetes mellitus type 2 in patients with arterial hypertension. The presence of diabetes mellitus type 2 with duration less than 5 years is associated with adaptive apelin-12 and obestatin high activity in patients with arterial hypertension. The presence of the disease with diabetes mellitus type 2 over 5 years in hypertensive patients accompanied by depletion of compensatory reactions of obestatin, and in long-term diabetes mellitus type 2 (over 10 years) - at the expense of obestatin and apelin-12 leads to an increase in the degree of left ventricular hypertrophy in hypertensive patients. Prospects of study is to analyze the apelin-12 and obestatin impact on the formation of a certain type of left ventricular remodeling in patients with hypertension and type 2 diabetes.
Keywords: arterial hypertension; diabetes mellitus type 2; left ventricular hypertrophy; apelin-12; obestatin